Potential phosphate solubilization and AIA production of Trichoderma spp. - Oliveira, Ariádila Gonçalves de; Chagas Junior, Aloisio Freitas; Santos, Gil Rodrigues dos; Miller, Luciane Oliveira; Chagas, Lillian França Borges (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2012)
This study aimed to evaluate the potential for production of indole acetic acid (IAA) and phosphate solubilization capacity, in vitro, by isolates of Trichoderma spp. From Trichoderma colonies grown on PDA (potato dextrose agar), disks were obtained approximately 8.0 mm in diameter, containing mycelium and spores were transferred to Erlenmeyer flask (250 ml) containing PD means (potato dextrose) and Fan (glucose and yeast extract) in the absence and presence of L-tryptophan as a precursor for biosynthesis of IAA. To evaluate the ability to solubilize phosphate, disks of approximately 8.0 mm in diameter with mycelium and spores, were transferred to Erlenmeyer flask (250 mL) containing NBRIP medium (modified). After colorimetric analysis, we determined the levels of IAA and soluble phosphorus. The phosphate solubilization, all strains tested were able to solubilize phosphate NBRIP means, with the highest concentration to isolate Tr-Dina (6.20 to 8.44 mg mL-1). For IAA, all isolates were capable of producing IAA in the two culture media evaluated and supplemented or not with L-tryptophan, with significantly higher with the use of L-tryptophan.